UPENA writing workshop - Lee, Nagarajah (Universiti Teknologi MARA, Sarawak, 2004)
The UPENA Cawangan Sarawak, in its endeavour to inculcate the writing culture among the staff, organized a workshop on writing, which was held from the 26 to 28 April 2004 at the Bilik Sarjana, UiTMCS. This activity is in line with the university's aim to promote writing of academic books, manuals, and manuscripts in the pursuance of its objective to become an internationally recognized university.